2020
DOI: 10.21203/rs.3.rs-109604/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Ultrasound-triggered Release of Calcein and Doxorubicin from HER2-targeted Liposomes in Breast Cancer Therapy

Abstract: The functionalization of liposomes with antibodies is a potential strategy to increase the specificity of liposomes and reduce side-effects of chemotherapeutic agents. The active targeting of Human Epidermal growth factor Receptor 2 (HER2) positive breast cancer cells can be achieved by coating liposomes with an anti-HER2 monoclonal antibody. In this study, we synthesized Calcein and Doxorubicin loaded immunoliposomes functionalized with the monoclonal antibody Trastuzumab. Both liposomes were characterized fo… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 46 publications
0
1
0
Order By: Relevance
“…Our previous in vitro studies have shown that applying low-frequency ultrasound (LFUS) enhances both drug release from the liposomes and their uptake by the cancer cells [21][22][23][24][25]. In this study, we investigate the use of liposomes as a carrier delivering Pharmaceutics 2021, 13, 2073 3 of 13 green graphene quantum dots to cancer cells and the effect of applying LFUS in enhancing the cellular uptake of free QDs and QDs loaded inside the liposomes by enhancing the permeability of both cellular and liposomal membranes.…”
Section: Introductionmentioning
confidence: 99%
“…Our previous in vitro studies have shown that applying low-frequency ultrasound (LFUS) enhances both drug release from the liposomes and their uptake by the cancer cells [21][22][23][24][25]. In this study, we investigate the use of liposomes as a carrier delivering Pharmaceutics 2021, 13, 2073 3 of 13 green graphene quantum dots to cancer cells and the effect of applying LFUS in enhancing the cellular uptake of free QDs and QDs loaded inside the liposomes by enhancing the permeability of both cellular and liposomal membranes.…”
Section: Introductionmentioning
confidence: 99%